Yogi Detox Tea: A Potential Cause of Acute Liver Failure. (24th October 2017) - Kesavarapu, Keerthana; Kang, Mitchell; Shin, Jaewook James; Rothstein, Kenneth
Abstract : We present a case of acute fulminant liver failure from a liver detoxification tea. We present a 60-year-old female with weakness, lethargy, scleral icterus, jaundice, and worsening mental status. She drank herbal tea three times a day for 14 days prior to symptom development. Liver tests were elevated. Remaining laboratory tests and imaging were negative for other etiologies. An ultrasound-guided liver biopsy showed submassive necrosis. A literature search on the ingredients shows six ingredients as having hepatotoxic effects and remaining ingredients as having very sparse hepatoprotective data. Healthcare professionals should discuss herbal medication and tea use and report adverse effects.